Pengaruh Persepsi Harga, Kualitas Produk Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Indihome Di Kota Batam - Siska Lorenza Br Hutauruk; David Sitorus (Komunitas Dosen Indonesia, 2022)
Alongs with the times, people need are to increase, especially at the fields of informations and communications technologies. Informations and communications technologies, which is initially very limited, has now become a necessity of life and an inseparable parts. One of these technologies, namely the internet, states that the internet is an abbreviation or abbreviation of interconnected network which is defined as a very large computer network, where the computer network consists of several small networks that are connected to each other. Based on the views of respondents that have been obtained from preliminary research, it appears that the main problem lies in the poor quality of IndiHome services which is the main cause of low consumer re-subscription intentions. The purpose of this study was to determine whether the perception of the price of product quality and the quality of service provided by IndiHome has an influence on consumers' subscription intentions. The technique used in this research is descriptive data analysis and quantitative data analysis.